Metric-Based Simulation Training to Proficiency for Endovascular Thrombectomy in Ischemic Stroke - Holtmannspötter, Markus; Crossley, Robert A.; Liebig, Thomas; Gallagher, Anthony G. (Frontiers in Neurology, 2022)
Ischemic stroke is one of the leading causes of death and of long-term disability in the Western Countries. Mechanical Revascularisation techniques are considered the standard of care for large vessel occlusive stroke. Traditional apprenticeship models involve doctors training skills on patients. Simulation platforms have long been recognised as an alternative to this. There has however been very little robust assessment of the training outcomes achieved with some of these platforms. At best, these simulations increase understanding of procedure process and may help improve some technical skills; at worst they may instil bad habits and poor technique. Prerequisite of any simulation process must be to teach what to do, with which devices, in the correct sequence as well as what NOT to do. It should provide valid metric-based feedback to the trainee that is objective, transparent, and fair for formative and summative performance feedback. This delivers a training programme, that measures performance progress of trainees against expert benchmarks. This benchmark must represent an evidence based, peer reviewed standard. We present a perspective for PBP training for thrombectomy based on our experience with the process of procedure characterisation, metric validation and early experience of using this approach for training to proficiency. Patient outcomes are not only determined by optimal performance in the angiosuite but an efficient patient procedure pathway. There will be value in utilising PBP training standard not only for the procedure itself but also the constituent elements of the stroke pathway to further improve treatment outcomes for ischemic stroke patients.